A didática de ensinar matemática através da realidade do aluno - Santos, Ricardo Martins dos (2019)
The present work was developed with the purpose of evaluating a different didactics of mathematics teaching, emphasizing the importance of being related to the theoretical knowledge, shared in the classroom and acquired by books, to the daily life of the student. We understand that this relationship facilitates the attainment and fixation of knowledge and, consequently, student learning, since its applicability will be experienced daily. The approach also helps the teacher to have a more accurate look at the development of their classes, in the methodologies used for each content. The process and methods of teaching mathematics, the role of the teacher, the importance of learning mathematics, the difficulties in the teaching and learning process, culminating in the everyday mathematics approach are reported. The research was carried out through a survey of the literature and through inquiries and doubts of the elementary school students of a school in the municipal school of the municipal school of Fortaleza and the state school of Ceará, representing, respectively, the José Ayrton Teixeira School and the Professora Adalgiza Bonfim Soares State School. It is concluded that mathematics is inserted and based on our most common routines, and that the utility's teaching emphasizes its value in addition to the formulas and resolution of exercises, showing its breadth, importance and benefit in the day-to-day of people